2024
DOI: 10.3390/nu16050660
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dynamic Relationship between the Gut Microbiome and Body Composition across the Human Lifespan: A Systematic Review

Ifigeneia Komodromou,
Eleni Andreou,
Angelos Vlahoyiannis
et al.

Abstract: This systematic review aimed to identify different gut microbiome profiles across the human lifespan and to correlate such profiles with the body composition. PubMed, Scopus, and Cochrane were searched from inception to March 2022. Sixty studies were included in this systematic review. Overall, the gut microbiome composition in overweight participants exhibited decreased α-diversity, decreased levels of the phylum Bacteroidetes and its taxa, and increased levels of the phylum Firmicutes, its taxa, and the Firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
1
1
0
Order By: Relevance
“…These results demonstrated that this organism is present in pediatric samples from patients as young as seven years old. This may be among the first studies to demonstrate that S. noxia may be present in patients this young, confirming observations from the few other studies of prevalence screenings revealing this organism among patients within similar age ranges [8,20]. In ad-dition, this study also found a clear association with age, with younger patients exhibiting decreased prevalence and many more of the older patients harboring this organism.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results demonstrated that this organism is present in pediatric samples from patients as young as seven years old. This may be among the first studies to demonstrate that S. noxia may be present in patients this young, confirming observations from the few other studies of prevalence screenings revealing this organism among patients within similar age ranges [8,20]. In ad-dition, this study also found a clear association with age, with younger patients exhibiting decreased prevalence and many more of the older patients harboring this organism.…”
Section: Discussionsupporting
confidence: 88%
“…Systematic reviews have shown strong evidence that gastrointestinal microbial composition may exhibit two-way relationships with overweight and obese patients, suggesting that more information regarding microbial constituents that influence caloric balance is of paramount importance [20]. Moreover, as intervention studies have demonstrated that microbial composition may be responsive to behavioral modifications such as intermittent fasting, more information will be needed regarding the species composition deemed most important to these phenomena [21].…”
Section: Introductionmentioning
confidence: 99%